Cooking Class : Stimulating Children’s Leadership - Ashari, Novita; Asqia, Nurul; Tadzkirah, Tadzkirah; Sari, Putri Indah; Anjani, Sadjena; Aprianti, Wiwi; Hasmiati, Hasmiati (AWLADY : Jurnal Pendidikan Anak, 2025)
The low leadership spirit of children due to no special learning carried out by the teacher in building the child's leadership spirit. The teacher only does the refraction to the children, such as when they start something, who dares to lead gymnastics, lead prayers, become priests during prayers and the culture of queuing when washing their hands. The purpose of this research is to build children's leadership spirit through cooking class. The research employed is descriptive qualitative. The results showed that the cooking class was able to improve four indicators of children's leadership, namely responsibility, independence, discipline, and children have a stand.